2020
DOI: 10.33545/pathol.2020.v3.i1f.196
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of apoptotic and proliferative markers in oral lesions and its clinicopathological significance

Abstract: Introduction: Oral cavity is prone to a myriad of changes with advancing age as well as a result of the environmental and life style related factors. Genetic abnormalities are the primary cause of dysplastic, metaplastic, and neoplastic changes resulting in an imbalance between molecular mechanisms which regulate apoptosis and cell proliferation. Evaluating these parameters may not only help in identifying the individuals who are at a greater risk of developing carcinomas, but also carry significant prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…Deng et al and Jairajpuri et al also observed similar expression pattern in group II and III; however, Thennevan et al suggested very limited expression in verrucous lesions. 12 17 Corresponding with the previous studies we concur that a proportional rise in the BCL2 expression from group I to III reflects its part in disease progression by increasing the survival rate of neoplastic cells and allowing clones of the neoplastic cells to proliferate and differentiate. In group IV, BCL2 immunoexpression was exaggerated and primarily confined to peripheral cells of the tumor islands similar to studies conducted by Juneja et al and Sudha and Hemavathy ( Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Deng et al and Jairajpuri et al also observed similar expression pattern in group II and III; however, Thennevan et al suggested very limited expression in verrucous lesions. 12 17 Corresponding with the previous studies we concur that a proportional rise in the BCL2 expression from group I to III reflects its part in disease progression by increasing the survival rate of neoplastic cells and allowing clones of the neoplastic cells to proliferate and differentiate. In group IV, BCL2 immunoexpression was exaggerated and primarily confined to peripheral cells of the tumor islands similar to studies conducted by Juneja et al and Sudha and Hemavathy ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…10 Cytological atypia is often debated as a feature in verrucous lesions. 10 Our study exhibited 50% cases of group II and 33.3% group III cases positive for atypia which was far lesser than the results obtained by Jairajpuri et al and Thomas and Barrett who observed a 69.2 and 66% positivity, respectively, for atypia in group II 12,37 (►Fig. 4B).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations